Implementation of Profile Matching Method in Student Major Information System at SMAN 4 Mataram - Nazmi Wardiani; Santi Ika Murpratiwi; Herliana Rosika; Royana Afwani; Sri Endang Anjarwani; Dwi Ratnasari (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2025)
Education is a crucial component in a country's development, and the quality of education is a key factor in determining national progress. In Indonesia, the Ministry of Education, Culture, Research, and Technology has implemented the Merdeka Curriculum, which provides students with greater flexibility to choose subjects based on their interests and talents. At SMAN 4 Mataram, the subject selection process starting in the second semester of grade 10 still faces challenges, such as students' difficulty in determining suitable majors and the lack of an integrated data management system. This study developed a decision support system based on the Profile Matching method to provide objective major recommendations by aligning students’ competencies with the criteria of each major. The system was developed using the Waterfall model to ensure a structured design process. Testing was carried out with White Box Testing to validate algorithm calculations, Black Box Testing to check system functionality, and User Acceptance Testing to assess user satisfaction. The results showed a very positive response from administrators (MOS 4.95 out of 5.00) and a positive response from students (MOS 4.00 out of 5.00). This research contributes a practical and flexible decision support solution specifically adapted to high schools implementing the Merdeka Curriculum. With this system, the major selection process is expected to become more efficient, integrated, and capable of providing recommendations that better align with students’ interests, talents, and academic potential. Key words: Education, Decision Support System (DSS), Majoring, Profile Matching, Waterfall.